Outcome and complications of endoscopic balloon dilatations in various types of ileocaecal and colonic stenosis in patients with Crohn's disease - Hagel, Alexander; Hahn, Anna; Dauth, Wolfgang; Matzel, Klaus; Konturek, Peter C.; Neurath, Markus; Raithel, Martin (Surgical Endoscopy, 2014)
We examined the outcome and the complications of endoscopic balloon dilatation (EBD) of ileocaecal and colonic strictures due to Crohn's disease.We examined 237 dilatation procedures in 77 patients with symptomatic ileocaecal and colonic stenosis regarding outcome, individual perforation risk, the need for further interventions, and other complications within a 10 years observation period.In 50 of 77 patients (64.9%), endoscopic dilatation procedures were successful within a median follow-up period of 24 months (25th and 75th percentile 10-38.5 months). Thirty five patients (45.5%) were successfully dilated with only one endoscopic procedure, while the remaining patients required two or more EBDs. Albeit the EBD, 27 patients of the whole cohort (35.1%) underwent surgical repair of the stenosis in due course. Overall complication rate was 7.6%, with postdilatation bleeding in 1.7% and abdominal pain longer than 24 h in 4.2%. Perforation occurred in 4 of 77 patients (5.2%), resulting in a perforation rate of 1.7% per intervention, or, more importantly, for the individual patient in a long-term perforation rate of 5.2% per patient, respectively.Endoscopic balloon dilatation (EBD) is a safe and effective approach to ileocaecal and colonic stenosis in approximately 65% of Crohn's disease patients. Even in case of recurrence, further endoscopic treatments can be undertaken. The perforation rate depending on the number of interventions is low, but for the individual patient a cumulative per patient perforation risk of 5.2% in the long-term should be considered during patient information and decisions for or against surgical interventions.
EVALuna2:1834